Acoustoelectric transient spectroscopy of microwave treated GaAs-based structures - Olikh, O.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The effects of microwave (2.45 GHz) treatment influence on the cross section for electron capture and the energy of the deep levels in the forbidden gap of GaAs monocrystals and n-n⁺ epitaxial structures have been investigated using acoustoelectric transient spectroscopy.